2019
DOI: 10.1021/jacs.9b10868
|View full text |Cite
|
Sign up to set email alerts
|

Sterically Controlled Late-Stage C–H Alkynylation of Arenes

Abstract: Phenylacetylenes are key structural motifs in organic chemistry, which find widespread applications in bioactive molecules, synthetic intermediates, functional materials, and reagents. These molecules are typically prepared from prefunctionalized starting materials, e.g. using the Sonogashira coupling, or using directing groupbased C−H activation strategies. While highly efficient, these approaches remain limited by their inherent selectivities for specific regioisomers. Herein we present a complementary appro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(42 citation statements)
references
References 96 publications
0
37
0
4
Order By: Relevance
“…For this purpose the deuterated benzoate substrate 1b-d5 was subjected to the catalyst system without adding the olefin reaction partner (note that a change of model substrate was required, since a background-H/D-exchange in known to occur for more electron-rich substrates). [11,28] We observed a substantial degree of H/D-exchange, thus proving the reversibility of the C-H activation step under the reaction conditions. Similarly, we subjected the same substrate to the reaction conditions in the presence of the olefin reaction partner and found that the H/D-exchange in the remaining substrate was strongly reduced.…”
Section: Resultsmentioning
confidence: 51%
See 2 more Smart Citations
“…For this purpose the deuterated benzoate substrate 1b-d5 was subjected to the catalyst system without adding the olefin reaction partner (note that a change of model substrate was required, since a background-H/D-exchange in known to occur for more electron-rich substrates). [11,28] We observed a substantial degree of H/D-exchange, thus proving the reversibility of the C-H activation step under the reaction conditions. Similarly, we subjected the same substrate to the reaction conditions in the presence of the olefin reaction partner and found that the H/D-exchange in the remaining substrate was strongly reduced.…”
Section: Resultsmentioning
confidence: 51%
“…[9,10] Recently our group has developed an arene-limited nondirected C-H alkynylation. [11] Furthermore, we could recently demonstrate that this design can also be applied to devise sterically controlled heteroarene functionalizations. [12] These studies hint at the tremendous synthetic potential of a broadly applicable generation of aryl-palladium species through nondirected C(sp 2 )-H activation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Das Testen von Säure/Base‐Kombinationen ergab, dass 1‐Adamantancarbonsäure (AdCOOH) und Kaliumcarbonat effiziente Aktivatoren für die C‐H‐Alkinylierung sind (Eintrag 4). Die Zugabe eines Silbersalzes als Halogenidfänger, eine Voraussetzung bei mehreren ähnlichen Transformationen, war für das Reaktionsergebnis nicht vorteilhaft (AgOAc, 48 % Ausbeute, Eintrag 5). Weitere Optimierungen zeigten, dass eine geringere Katalysatormenge gut toleriert wurde und die Ausbeute sogar leicht auf 84 % verbesserte (Eintrag 6).…”
Section: Methodsunclassified
“…10 Furthermore, we described an analogous alkynylation later that year. 11 Importantly, all of these methods used the arene as the limiting reagent and can therefore, in principle, be used for late-stage functionalization. In our study on the Fujiwara-Moritani reaction, we hypothesized that this should be possible, but the suitability of our protocol for the late-stage olefination of arenes was not experimentally evaluated.…”
Section: Cluster Synlettmentioning
confidence: 99%